SERVICE LEARNING FOR THE CREATION OF A HOLISTIC GRADUATE: A CASE STUDY OF TAYLOR’S UNIVERSITY COMMUNITY SERVICE PROGRAMME - Marzura Abdul Malek; Usha Devi Rajaratnam (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Community service is a way to engage students in active learning, making the learning process more satisfactory and meaningful. Zlotkowski (1998) recommended the academicians to focus on active learning strategies for a greater impact on social service learning: learning reflection. High-Quality service is obtained from reflection on learning experience as stated by Dewey (1916) where personal experience gives the theory a different meaning when analysis and critical examination on experience are done. This paper examines the educational values and aims of the students participating in community service projects from Jan – June 2017 from their weekly reflective journals. For the weekly reflective journals to be educative, a content analysis was done based on Dewey’s four conditions of inquiry-based learning process of 1) it must generate interest among the students 2) it must be intrinsically worthwhile to the students c) it must create a curiosity and a demand for information when a problem arises and d) it must cover a specific time and foster development over time. A minimum of 5 reflections was done by each student. The findings of the study show an astounding result of unprecedented student behaviour towards the community service.